Decodependence : a romantic tragicomic - Ash, Lila (Princeton Architectural Press, 2023)
Author and New Yorker cartoonist Lila Ash's vulnerable and funny graphic memoir about her attempts to decode her life's relationships through the lens of her recovering codependency.